FAKTOR-FAKTOR PENENTU PROFITABILITAS DENGAN PERAN KECUKUPAN MODAL SEBAGAI INTERVENING PADA BANK SYARIAH - Pertiwi, Tanza Dona; Kholison, Rohmatul Farokhah; Rusgianto, Sulistya (Jurnal Ekonomika dan Bisnis Islam, 2024)
Banks' operational quality heavily depends on their financial performance, which serves as a primary parameter for assessing their contribution to the economy and social welfare. This study looks at how financing risk (NPF), third-party funds (DPK), efficiency (BOPO), and liquidity (FDR) affect profitability (ROA), with capital adequacy ratio (CAR) being a variable that works in between for Islamic banks. The findings, which were conducted on a sample of 12 Islamic banks in Indonesia during the 2019–2023 period using quarterly data, indicate that NPF and DPK are not significant to ROA but influence CAR. BOPO negatively affects ROA, while FDR is not significant to ROA but significant to CAR. CAR acts as an intervening variable, strengthening the relationship between these factors and ROA. This underscores the need for Islamic banks to pay greater attention to managing financing risk, third-party funds, operational efficiency, and liquidity to maintain the balance between capital and profitability. The implications of this study underscore the critical importance of risk and capital management in Islamic banking, as success in these areas will impact the sector's competitiveness and contribution.